{On the characterization of arg max {U (X) │ PX =0 - Aloqeili, Marwan (مجلة جامعة القدس المفتوحة للبحوث الإنسانية والاجتماعية, 2017)
In this paper, we use exterior differential calculus notations to get the conditions that characterize the solution to the utility maximization problem subject to the constraints Px = 0Rm where P is an m × n matrix.